Educational Quality : Defining What's Important - Heneveld, Ward (World Bank, Washington, DC, 2012)
Planning and monitoring the quality of primary education in sub-Saharan Africa takes as its starting point the conviction that improvements in the quality of education must focus on the school as the unit of change. Through a review of the qualitative research literature on school improvement and the more quantitative literature on school effectiveness, a conceptual framework that identifies generic factors that determine school effectiveness is formulated. Drawing from the literature, detailed definitions and indicators relevant to sub-Saharan Africa are presented for each of the factors. The paper then describes, with some examples, how the conceptual framework of factors, definitions, and indicators can be used in the region to plan improvements in the quality of primary education, to conduct situation analyses and sector work on school quality, and to monitor and evaluate educational reforms. The paper concludes with an assessment of the strengths and weaknesses of these materials and a reminder that they must be locally adapted if they are to prove useful in improving the quality of education for Africa's children.